Tax Compliance Behavioral Intervention: Tax Reminder Letters for Tax Return’s Filing - Afiat Ria Nabati; Benedictus Raksaka Mahi (Program Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to analyze whether the behavioral intervention, i.e., by sending tax reminder letters to the corporate taxpayers (WP) in Indonesia improves compliance in the filing of tax returns (SPT). It uses probit estimation on the panel data of Corporate Taxpayer’s filing of SPT at Medium Tax Office throughout Indonesia within 2010-2016. The estimation results indicate that reminder letters have more positive impacts to increase the probability of tax return filing for WP with the status of Taxable Entrepreneurs (PKP) than non-PKP. Based on the domicile of WP, tax reminder letters to WP in Jakarta show lower effects than if they were given to WP in Sumatra, while a more positive influence is shown by letters to WP in Java other than Jakarta, Bali Nusa Tenggara, Kalimantan, and Sulawesi Maluku Papua. Regarding business category, only WP of the Construction category demonstrate different impact, which is significantly less effective than the letters issued to WP in the Agriculture category. Overall, tax reminder letters containing the message of the imposition of sanctions effectively encourage the change of WP's behavior to be more compliant in filing SPT for WP status as PKP, located outside Jakarta, and in the categories other than Construction.